Identity formation, online resources, and young adults with type one diabetes mellitus : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University, Wellington, New Zealand - Eady, Anna (Massey University, 2011)
One of the fundamental processes of transitioning from being a teenager to a young emerging adult is the construction of a gendered identity. For a young emerging adult who has been diagnosed with type one diabetes mellitus, an extra layer of complexity has been added to this task. Previous research has found there to be a paucity of information about the interactions between type one diabetes mellitus and gendered identity formation, especially in the young emerging adult population in New Zealand. This study considered how living with type one diabetes mellitus influenced a young adult’s gendered identity construction, and how this identity is portrayed and shaped through the use of social networking internet sites. It also investigates what information is readily available online about type one diabetes mellitus for this population, and whether it mirrors their experiences. Interviews with six young New Zealand adults who had a diagnosis of type one diabetes mellitus were carried out, and four media articles about type one diabetes mellitus were accessed online. A grounded theory analysis was performed using a constant comparison approach. This resulted in a framework which explained how control over the chronic condition is the most important factor for the participants’ identity formation, and how gender issues, support from others and being supportive of others, perceptions of others, and the restrictions type one diabetes creates feeds into this sense of control. It also explained how social networking sites, a now popular mode of internet socialising, are an important mode of socialising and accessing non-type one diabetic support for the individuals studied. If a young adult has control over their condition, they are able to confidently incorporate it into their identity and be happier and healthier as a result. Insight into how this population manages their identity construction whilst incorporating their diagnosis, and also how social networking sites are utilised by this population, has implications for the provision of care by health professionals.
Keywords: Diabetes mellitus; Diabetes; Identity formation; Youth; Young adults; Gender identity; Online social networks; Online resources; Teenagers; New Zealand; Social networking online